Protecting Nepal’s Biodiversity in the Context of Sustainable Development Goal 15 - Berardino, Frances R; Walsh, Christine A. (Molung Educational Frontier, 2024)
With high elevations and a variety of ecosystem classifications ranging from wetlands to alpine regions, Nepal is one of Earth’s most ecologically diverse countries. However, with global trends of declining biodiversity, Nepal’s ecological diversity is also at risk. The Sustainable Development Goals (SDGs) are a set of 17 global goals created in the hopes of developing our planet for the betterment of both people and the planet. SDG 15 – Life on Land focuses specifically on protecting the land we live on and the non-human world. Considering Nepal’s high biodiversity, it is essential to protect biodiversity for both the Nepali people and the global community at large. Nepal has made a bold commitment to fulfilling SDG 15, including designating vast areas as protected areas and employing community-based conservation strategies and community based approaches. The following paper is a narrative review of empirical-based literature focused on understanding the complex landscape of biodiversity in Nepal and the implications for achieving SDG 15.